Understanding the Jokowi effect during Indonesia’s 2024 presidential election: an integrative model of incumbency advantage - Ais Shafiyah Asfar; Muhammad Asfar; Dimas Lazuardy Firdauz; I Gede Wahyu Wicaksana; Rachmah Ida; Aribowo (Cogent Social Sciences)
Incumbency advantage in elections has been interpreted as the incumbent’s ability to allocate and leverage available resources to build a stronger electoral position than their opponents. This concept is widely recognised as one of the most relevant frameworks for understanding the power dynamics of sitting presidents during election periods. However, the prior studies have not thoroughly explored scenarios where the incumbent president does not seek re-election but instead allocates their power, resources, and accumulated political capital to enhance their equity of incumbency while signaling their heir. This study examines the phenomenon of incumbency effects in the case of Indonesia’s 2024 presidential election, focusing on the impact of President Joko Widodo’s (Jokowi) to Prabowo-Gibran victory. The study introduces a novel conceptual model grounded in four theoretical perspectives: retrospective voting, cost-benefit voting, signaling theory, and political valence. The findings indicate that the so-called Jokowi effect on the 2024 election is undeniable. Applying these four perspectives significantly contributes to developing the academic discourse on incumbency effects in elections. The Jokowi effect further enriches the Political Science literature, particularly in understanding the influence of a sitting president on the dynamics of presidential candidate competition, voter behavior, and the broader implications for Indonesia’s vulnerable democracy.